Diagnostic errors in pulmonary hydatid cyst complicated by spontaneous rupture in the bronchus: clinical case presentation - Nicoalae, Dogotari; Igor, Ambros; Virginia, Negru; Stanislav, Babuci (International Journal of Research in Medical Sciences, 2023)
Diagnosis and treatment of a pulmonary hydatid cyst complicated by rupture are difficult, especially in cases of late presentation. In this context, the authors report a case of spontaneous rupture of a large pulmonary hydatid cyst diagnosed in a patient 12 years old who was directed to our institution with the preventive diagnosis of a right lung abscess rather late and successfully treated by surgery. The authors conclude that the disease was initially clinically misdiagnosed as a respiratory infection, then a lung abscess, the radiological examination being avoided at the initial stages of the disease. Diagnostic errors impose the need to familiarize physicians with hydatid disease to improve awareness. The padding procedure completed with filling used for resolving residual postechinococcectomy cavities in cases of pulmonary hydatid cyst complicated by rupture is an effective method that allows reducing the postoperative morbidity and the length of hospitalization. However, some pneumofibrotic sequelae associated with changes in pulmonary perfusion persist for a long time after surgery.